Routing protocol based key management schemes in manet: a survey - K.R, Shibu; Pramila R, Suji (International Journal of Engineering and Technology, 2018)
Mobile ad-hoc networks (MANETS) are infrastructure less networks and the topology of this network is always changing. The nodes can enter and leave the network at any time. These networks require a high security in communication, as its application demands so. Effective key management is the only technique, which can implement to secure the nodes in communication. In adhocnetworks there is no central controller or router such as in wired network. This will make this network more vulnerable to attack. The intruders can easily enter the net-work and can manipulate the contents easily. Traditional key management schemes will not fit for this type of networks. This article, discuss various key management schemes based on routing protocols in mobile ad-hoc network (MANET). It also analyses them in terms of the security and applicability.Â Â
Keywords: Manet; Key Management; CA; Certificate Chaining